Complex tissue regeneration in Lophuromys reveals a phylogenetic signal for enhanced regenerative ability in deomyine rodents - Brennan Riddell; Molly McDonough; Adam Ferguson; John M. Kimani; Thomas R. Gawriluk; Chi Peng; Stephen G. Kiama; Vanessa O. Ezenwa; Ashley W. Seifert (Proceedings of the National Academy of Sciences, 2025)
Identifying why complex tissue regeneration is present or absent in specific vertebrate lineages has remained elusive. One also wonders whether the isolated examples where regeneration is observed represent cases of convergent evolution or are instead the product of phylogenetic inertia from a common ancestral program. Testing alternative hypotheses to identify genetic regulation, cell states, and tissue physiology that explain how regenerative healing emerges in some species requires sampling multiple species among which there is variation in regenerative ability across a phylogenetic framework. Here, we interrogate tissue healing across eleven rodents and show that brush-furred mice ( Lophuromys zena ) are capable of musculoskeletal regeneration where new tissue faithfully maintains axial polarity and tissue identity as previously observed in spiny mice ( Acomys spp. ). In contrast, we find that all nondeomyine rodents heal identical ear pinna injuries via fibrotic repair with scar tissue. Together, these data reveal a phylogenetic signal for enhanced regenerative ability in Deomyinae which is key to testing evolutionary hypotheses about the emergence of regenerative ability in mammals.